Dynamic assessment of sternoclavicular joint instability using four‐dimensional computed tomography. Issue 2 (25th February 2019) - Goh, Yin Peng; Kamali Moaveni, Ash; Hoy, Gregory; Tate, Julie; Rotstein, Andrew
Summary: Chronic post‐traumatic sternoclavicular joint (SCJ) instability can be debilitating and result in restriction of normal daily activities. The diagnosis can be difficult to make clinically or with the use of static imaging modalities. Wide‐volume dynamic four‐dimensional computed tomography (4D CT) can confidently diagnose chronic post‐traumatic SCJ instability. This can aid surgeons in pre‐operative planning and help to triage patients into surgical or non‐surgical candidates. We propose that 4D CT to be a routine pre‐operative imaging in patients with chronic post‐traumatic SCJ instability.